Direct Benzyl Alcohol and Benzaldehyde Synthesis from Toluene over Keggin-Type Polyoxometalates Catalysts: Kinetic and Mechanistic Studies - Allam Djaouida; Mansouri Sadia; Hocine Smaïn (Journal of Chemistry)
The catalytic activity of various Keggin polyoxometalate catalysts has been investigated in the gas-phase partial oxidation of toluene to produce benzyl alcohol and benzaldehyde. The catalyst systems HPMo12O40, HPMo11VO40, FePMo12O40, and PMo11FeO39 were prepared and characterized by FT-IR, UV-visible, SEM, XRD, TGA, and cyclic voltammetry. The acid/base properties were evaluated using the decomposition of isopropanol. Catalytic studies were carried under atmospheric pressure and over the temperature range 200°C–350°C, using carbon dioxide as a mild oxidant. Toluene conversion and product distribution depend mainly on the catalyst composition and operating conditions. In addition to benzaldehyde, benzyl alcohol is obtained with a high selectivity on the PMo11FeO39 catalyst. The kinetic data show that the reoxidation of the reduced catalyst is the rate-limiting step for the partial oxidation reaction of toluene.